ANALISIS DIKSI DAN CITRAAN DALAM KUMPULAN PUISI ANAK MAJALAH BOBO TAHUN 2016 - Fadhilatun Hayatunnufus (Kelasa, 2017)
AbstractThis research entitled "An analysis on Dictions and Imageries in a Collection of Child Poems in BoboMagazines in 2016." The formulation of the problem in this study is what types of imagery containedin the poetries of children published in Bobo magazine. The purpose of this study is to describeany kinds of imagery contained in the poetry of children in Bobo magazine. The type of thisresearch is a qualitative research. The technique used in data collection is a literary study from 15poems. To analyse the data, the researcher used a descriptive analytic method which is done bydescribing facts and analyzing them. The results of this study indicate that the selection of word inthis child’s poem uses denotative words and easy to understand by readers and there are only afew poems that use connotative words in Bobo magazine. Imageries contained in the poetries ofchildren in Bobo magazine is visual imagery, kinestethic imagery, olfactory imagery, gustatory imagery,and tactile imagery. The most dominant image used by children in making poetry in Bobomagazine is visual imagery. AbstrakPenelitian ini berjudul “Analisis Diksi dan Citraan Puisi Anak dalam Majalah Bobo Tahun 2016”.Rumusan masalah dalam penelitian ini adalah citraan apa saja yang terdapat dalam puisi anakyang dipublikasikan dalam majalah Bobo. Tujuan penelitian ini adalah untuk mendeskripsikancitraan apa saja yang terdapat dalam puisi anak dalam majalah Bobo. Jenis penelitian ini adalahpenelitian kualitatif. Teknik pengumpulan data yang digunakan adalah teknik studi pustaka.Pengolahan data penelitian dengan metode deskriptif analitik yang dilakukan denganmendeskripsikan fakta-fakta dan menganalisisnya. Hasil penelitian ini menunjukkan bahwapemilihan kata dalam puisi anak ini menggunakan kata-kata denotatif dan mudah dimengerti olehpembacanya serta hanya ada beberapa puisi yang menggunakan kata-kata bermakna konotatifdalam majalah Bobo. Citraan dalam puisi anak pada majalah Bobo terdiri dari citraan penglihatan,gerak, penciuman, pencecapan, dan perabaan. Citraan yang paling dominan digunakan oleh anakdalam membuat puisi pada majalah Bobo adalah citraan penglihatan.